Classroom Action Research: Implementation of the Student Teams Achievement Divisions Type Cooperative Learning Model to Improvee Student Discipline - Mariani Meri Lumban Gaul; Elisa Br Ginting (Postgraduate, University of Mataram, 2025)
This study aims to improve student discipline through the application of the Student Teams Achievement Divisions (STAD) cooperative learning model in Catholic Religious Education at SMA RK 2 Kabanjahe. The research was conducted using Classroom Action Research (CAR) based on the Kemmis and McTaggart model in two cycles, each consisting of planning, action, observation, and reflection. The subjects were 36 eleventh-grade students from one class. Data were collected through observation sheets, discipline questionnaires, and documentation. Discipline indicators included Punctual attendance, Timely assignment submission, Compliance with classroom rules, Orderliness during the learning process, Honesty in completing assignments. The results showed gradual improvement: the average discipline score increased from 57.60% in the pre-cycle (based on combined questionnaire and observation scores), to 70.40% in the first cycle, and 88.00% in the second cycle. These findings suggest that the STAD model enhances discipline by engaging students in structured teamwork, promoting responsibility for group performance, and encouraging consistent participation. In this way, STAD helps strengthen classroom discipline in Catholic Religious Education through collaborative and accountable learning.